2019
DOI: 10.1038/s41467-019-09523-0
|View full text |Cite
|
Sign up to set email alerts
|

Specific inhibition of splicing factor activity by decoy RNA oligonucleotides

Abstract: Alternative splicing, a fundamental step in gene expression, is deregulated in many diseases. Splicing factors (SFs), which regulate this process, are up- or down regulated or mutated in several diseases including cancer. To date, there are no inhibitors that directly inhibit the activity of SFs. We designed decoy oligonucleotides, composed of several repeats of a RNA motif, which is recognized by a single SF. Here we show that decoy oligonucleotides targeting splicing factors RBFOX1/2, SRSF1 and PTBP1, can sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 66 publications
3
64
0
1
Order By: Relevance
“…This strategy was successfully used to target the activity of the splicing factors RBFOX1/2, PTBP1, and SRSF1. Importantly, the intracranial injection of an SRSF1-targeted DRO in a GBM mouse model decreased the oncogenic properties of cancer cells by reverting the splicing of oncogenic splice variants of SRSF1-target genes (INSR, U2AF1, MKNK2, USP8; see Table 2) [128]. These observations suggest that RNA-based therapeutic strategies may be useful to counteract brain tumorigenesis.…”
Section: Therapeutic Approachesmentioning
confidence: 97%
See 2 more Smart Citations
“…This strategy was successfully used to target the activity of the splicing factors RBFOX1/2, PTBP1, and SRSF1. Importantly, the intracranial injection of an SRSF1-targeted DRO in a GBM mouse model decreased the oncogenic properties of cancer cells by reverting the splicing of oncogenic splice variants of SRSF1-target genes (INSR, U2AF1, MKNK2, USP8; see Table 2) [128]. These observations suggest that RNA-based therapeutic strategies may be useful to counteract brain tumorigenesis.…”
Section: Therapeutic Approachesmentioning
confidence: 97%
“…In some cases, these approaches have been also applied to brain tumors, eliciting promising pre-clinical results. In particular, ASOs targeting both protein-coding and regulatory non-coding RNA [126,127], sense oligonucleotides acting as decoy for specific splicing factors [128], or small drugs that modulate the activity of the spliceosome [53] have been tested in brain tumor models.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…While this contribution focuses on TFs binding to genomic decoy sites, these results are applicable to other classes of proteins, for example RNA-binding proteins binding to sites on RNA. [112][113][114][115] Our results show that degradation of decoy-bound TFs critically impacts both the mean and noise levels of the free TF pool. More specifically, while the average number of free (available) TFs monotonically decrease with increasing decoy abundance, the noise levels can sharply increase at low/intermediate decoy numbers before attenuating to Poisson levels as N → ∞ (Fig 2).…”
Section: Discussionmentioning
confidence: 71%
“…The sequence analysis showed that there were several motifs (UCUCU) in the LHFPL3-AS1 precursor and LHFPL3-AS1-long (Fig. 6A ), which could be bound by PTBP1 protein 20 , suggesting that the splicing of LHFPL3-AS1 regulated by PTBP1 contribute to the biogenesis of LHFPL3-AS1-long.
Fig.
…”
Section: Resultsmentioning
confidence: 99%